Transgenerational Metabolic Determinants of Fetal Birth Weight - Agius, R.; Savona-Ventura, C.; Vassallo, J. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Infants born with a higher birth weight have long been associated with an increased incidence of developing the metabolic syndrome starting from early childhood and persisting into adult life. Such risk factors include genetic tendencies as well as environmental factors. Of these, certain maternal anthropometric characteristics such as obesity or carbohydrate intolerance alter the intrauterine environment to one of nutritional plenty, thus impacting on intrauterine development. This hypernutrition pathway has led to the hypothesis of fuel mediated teratogenesis’ and an obesogenic environment.The aim was to identify a relationship across 3 generations relating to body weight and birth weight in order to identify whether a genetic and/or nutritional role are involved in the observed transmission.The study utilized 2 clinical databases. The first consisted of a cohort of 182 women born in 1987 and who delivered a child between 2004–2010 [2nd Generation]. A total of 233 infants were born [3rd Generation]. This was further linked to another database of women who had delivered a child in 1987 [1st Generation]. The birth weight of the 2nd and 3rd generations and the pre-pregnancy body mass index (BMI) of the 1st and 2nd generation were registered as was the development of features of the metabolic syndrome in the 1st generation population. The 1st generation population was subdivided into 2 groups based on the BMI: BMI <25 kg/m2 (n=76) and BMI >=25 kg/m2 (n=106). The mean birth weights and pre-pregnancy BMI of the subsequent generations were compared using the student t-test.There was no direct transgenerational link between the first generation BMI and third generation birth weight. Rather, birth weight was directly linked to maternal BMI. Furthermore in this study we also studied the presence of metabolic syndrome in first generation mothers. The presence or absence of metabolic syndrome did not cause any statistically significant difference in the birth weight of 2nd and 3rd generations.This study supports previous reports that environmental factors play a key role in determining fetal birth weight. Identifying women with a higher pre-pregnancy BMI and educating them with regards to dietary modification in order to reduce body weight prior to pregnancy would contribute towards less adverse outcomes to the mother and her child in both the short and the long term.
Keywords: fetal birth weight; body mass index; metabolic syndrome